Indirectness in English requests among Malay university students - Mohd Khalib, Farahnaz; Tayeh, Asma (Elsevier, 2014)
Communication serves as the main medium to connect human beings so that they can live in harmony. There are numerous ways to communicate effectively, and one of them is by making polite requests. Adopting the Discourse Completion Test (DCT), 40 questionnaires were distributed to 40 respondents from two higher learning institutions located in Selangor. The results showed that conventionally indirect strategies were preferred by students when making requests to their lecturers, and even to their friends. Therefore, the findings indicate that the Malay culture conforms to Brown and Levinson's theory on face which highlights that in order to keep either positive or negative face on FTA (Face Threatening Acts), politeness or indirectness strategies are employed.